The joint effects of audit committee financial expertise and auditor industrial expertise on the quality of earnings4hBomi Song - Bomi Song (Global Business & Finance Review (GBFR), 2021)
Purpose: The aims of this study are to investigate the joint effects of financial experts on audit committees (ACs) and industry expert auditors on earnings quality, and to investigate whether the joint effects differ based on subtypes of financial experts on ACs and the mixture of those subtypes. Design/methodology/approach: This study measures AC financial expertise and auditor industrial expertise using indicator variables. To measure the quality of earnings, this study employs the approach of Kothari et al. (2005). Findings: The study finds evidence that only the interaction between AC financial expertise and auditor industrial expertise has a positive effect on earnings quality. Specifically, earnings quality improves only when firms have accounting professors or finance experts (excluding finance professors) on ACs, and at the same time, when firms receive external audit from an industry specialist auditor. The study also finds that the positive association becomes obvious when ACs have both accounting and non-accounting experts. More importantly, the positive association is stronger when ACs have both non-accounting experts and more than one type of accounting experts. These results suggest that it is crucial that internal and external audit functions work cooperatively rather than separately, and that ACs include both non-accounting experts and several types of accounting experts. Research limitations/implications: The effects of AC financial expertise on accounting information quality may vary depending on how ACs are actually operated. Thus, it would be worthwhile for future research to explore the effectiveness of ACs in consideration of the operation of ACs. Originality/value: Contrary to prior research, this study examines the interplay of AC financial experts and industry specialist auditors. In addition, this study examines the interplay by using subtypes of financial experts on ACs and the combination of those subtypes. This study can be valuable to policy makers, academicians and investors by providing a more comprehensive view of the effectiveness of internal and external audits.
Keywords: 650; Audit committee; Financial expertise; Auditor industrial expertise; Corporate governance; Earnings quality